Frequência de colheita em pastos de Megathyrsus maximus cv. Sempre-Verde - Cavalcante, Filipe Souza (2018)
The objective of this work was to evaluate the frequency effects of Megathyrsus maximus cv. The treatments were characterized by harvest frequencies, being: fixed periods of 28 days, whenever the canopy intercepted 90%, or 95% of the incident light, following a completely randomized design with four replicates. It was observed at pre-cut height that the 28-day treatment had a higher mean (104.61 cm), with lower values (P <0.0001) and 90% IL treatment (80.46 cm). At the post-cut period, the treatment of 28 days of rest also presented the highest mean value (63.19 cm), with frequencies of 90 and 95% IL, not differing from each other. The light intercept, in the pre-cut condition, presented differences between the treatments (P <0.0001), with a higher mean value being observed in the treatment of 28 days (95.81%) and lower in 90% IL (90, 83%). For light interception, the treatment of 28 days had a higher value 81.63% of IL (P <0.0001), treatment 95% had a value of 67.74%, and treatment 90%, 74.48% of IL. Regarding the leaf angle, the treatments showed no differences, both in the pre-cut and post-cut conditions (P = 0.435). The leaf area index, in the pre-cut condition, presented a difference (P> 0.0001) between the treatments, in which the 28 days presented the highest value (4.13), the 95% IL presented an intermediate value ( 3.79) and the treatment of 90% IL presented the lowest value (3.37). The highest post-cut leaf area index was observed in the 28-day treatment (2.03), and the treatments were treated by similar IL (1.46 and 1.66 for 90 and 95% IL, respectively), not differing from each other . Regarding the rate of tiller emergence, the treatment of 90% IL presented the highest mean value (P = 0.05) (0.58), with the lowest value being observed in the treatment of 28 days (0.4), in that of 95% IL was similar to the others (0.47). Regarding the rate of tillering treatments did not differ statistically between them (P = 0.11). Regarding the tiller survival rate, the treatment of 90% IL showed a lower rate, the treatment of 95% IL did not differ statistically from the others for tiller survival rate, being the highest value observed in the treatment 28 days. Regarding the population density of tillers the results obtained in this study did not present statistical differences between them. With an average value of 452.7 tiller.m-2. Regarding the number of cycles, 90% IL presented the highest number, with 11, the treatment of 95% IL presented a number of intermediary cycles (10 cycles). The treatment was managed with 28 days, which presented the fewest cycles, (9 cycles). It was observed a high degree of correlation between light interception with canopy height (r = 0.72), between light interception and leaf area index (r = 0.78) and between leaf area index and canopy height (r = 0.81). The treatment handled with 90% IL presented the best results, as it presented a higher number of harvest cycles, a shorter rest period and a greater renewal of tillers in this system. In addition, pastures managed with 90% IL can be harvested when they reach 80.46 cm and lowered with 48.37 cm in height.